Association of obstructive sleep apnea plus hypertension and prevalent cardiovascular diseases: A cross-sectional study. Issue 39 (September 2016) - Wang, Ling; Cai, Anping; Zhang, Jiawei; Zhong, Qi; Wang, Rui; Chen, Jiyan; Zhou, Yingling
Abstract : Abstract: Current study sought to evaluate the associations of obstructive sleep apnea (OSA) plus hypertension (HTN) and prevalent cardiovascular diseases (CVD). This was a cross-sectional study and a total of 1889 subjects were enrolled. The apnea-hypopnea index (AHI) was measured by polysomnography and OSA degree was classified as mild (AHI 5–14.9) and moderate-severe (AHI ≥ 15), and AHI < 5 was considered no-OSA. Mean and lowest oxyhemoglobin saturation (SaO2 ) was detected by pulse oximetry. Between-group differences were assessed and logistic regression analysis was used to analyze the association of OSA plus HTN and prevalent CVD. Compared to normotensive subjects, hypertensive subjects were older and had higher body mass index (BMI), neck girth, waist–hip ratio, AHI, and low-density lipoprotein cholesterol (LDL-C) level. Conversely, mean and lowest SaO2 levels were significantly lower. Logistic regression analysis showed that in an unadjusted model, compared to subjects with no-OSA and no-HTN (reference group), the association of HTN plus moderate-severe-OSA and prevalent CVD was the most prominent (odds ratio [OR]: 2.638 and 95% confidence interval [CI]: 1.942–3.583). In normotensive subjects, after adjusted for potential covariates, the associations of OSA (regardless of severity) and prevalent CVD were attenuated to nonsignificant. In hypertensive subjects, however, the associations remained significant but were reduced. Further adjusted for mean and lowest SaO2, the associations remained significant in HTN plus no-OSA (OR: 1.808, 95% CI: 1.207–2.707), HTN plus mild-OSA (OR: 2.003, 95% CI: 1.346–2.980), and HTN plus moderate-severe OSA (OR: 1.834, 95% CI: 1.214–2.770) groups. OSA plus HTN is associated with prevalent CVD, and OSA may potentiate the adverse cardiovascular effects on hypertensives patients but not normotensives.